Exploring the Efficacy of Omega-3 Fatty Acid Supplementation in Dry Eye Disease: A Comprehensive Review - Martyka, Anna; Kubicka-Figiel, Martyna; Taborska, Nina (Journal of Education, Health and Sport, 2024)
Introduction Dry eye syndrome, as defined by TFOS, is a multifactorial ocular surface disease with tear film instability, hyperosmolarity, inflammation, and neuro-sensory abnormalities. With a prevalence between 6.5% and 52.4%, it poses a substantial public health challenge, significantly affecting patients’ quality of life. Omega-3 fatty acid supplementation is often suggested by clinicians as an adjunctive treatment, offering potential benefits across various levels. Aim of the study The purpose of the study was to investigate the effect of oral supplementation of omega-3 fatty acids on the treatment of dry eye syndrome. Materials and methods Literature selections of PubMed and Google Scholar databases from the last seven years (2016-2023) were performed. Articles were searched in English using the following keywords: dry eye disease; omega-3; fatty acid. Results Omega-3 fatty acids may have benefits in the treatment of dry eye syndrome, as argued by a number of potential mechanisms of action. However, the literature does not agree on the efficacy of their use in the treatment of dry eye syndrome, and thus there is insufficient evidence to bring omega-3 acids into the standard of treatment for dry eye syndrome. Conclusion Studies on the effect of oral supplementation of omega-3 fatty acids on the treatment of dry eye syndrome are at an early stage and need to be continued to improve knowledge. There is a need for further long-term studies to standardize conclusions about the efficacy of these acids in reducing dry eye symptoms.